ANALISIS RASIO KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PEMERINTAH DAERAH PENERIMA DANA OTONOMI KHUSUS (Studi Kasus Pada Kabupaten/Kota Se-Provinsi Papua 2017-2021) - Hertin Khalifatun Nisa Arifah; Nurul Hidayat; Samsul Arifin (Kompetensi (Competence : Journal of Management Studies), 2023)
ABSTRACTThis study aims to analyze the financial performance of districts/cities throughout Papua Province in 2017-2021. Financial performance is seen from the ratio of independence, effectiveness, efficiency and growth. This research is a type of quantitative research. The sample in this study is reports on the realization of district/municipality budgets throughout the Papua Province, totaling 29 districts/cities. The data used in this study is secondary data, namely from reports on the realization of district/city budgets throughout the Province of Papua which are calculated using the analysis method of the ratio of independence, the ratio of effectiveness, the ratio of efficiency and the ratio of growth. The results of this study indicate that the ratio of independence in the last five years is very low with a high level of dependence on external parties, the ratio of effectiveness is very high, the ratio of efficiency shows that PAD is not efficient in collecting PAD, the ratio of growth shows a fluctuating trend.Keywords: Local government, financial performance, financial ratios (independence ratio, effectiveness ratio, efficiency ratio and growth ratio). ABSTRAKTujuan dari penelitian ini adalah untuk mengukur kinerja keuangan daerah Kabupaten/Kota se-Provinsi Papua pada tahun 2017-2021. Kinerja Keuangan dilihat dari rasio kemandirian, efektivitas, efisiensi dan Pertumbuhan. Penelitian ini merupakan jenis penelitian kuantitatif. Sampel pada penelitian ini ialah laporan realisasi APBD Kabupaten/Kota Se-Provinsi Papua yang berjumlah 29 Kabupaten/Kota. Data yang digunakan dalam penelitian ini adalah data sekunder  yaitu dari laporan realisasi APBD Kabupaten/Kota se-Provinsi Papua yang dihitung menggunakan metode analisis rasio kemandirian, rasio efektifitas, rasio efisiensi dan rasio pertumbuhan. Hasil penelitian ini menunjukkan bahwa rasio kemandirian pada lima tahun terakhir sangat rendah dengan tingkat ketergantungan terhadap pihak eksternal masih tinggi, rasio efektivitas sangat tinggi, rasio efisiensi menunjukkan dalam pemungutan PAD tidak efisien, rasio Pertumbuhan menunjukkan tren fluktuatif.Kata Kunci : Pemerintah daerah, Kinerja keuangan, Rasio Keuangan (Rasio Kemandirian, Rasio Efektivitas, Rasio Efisiensi dan Rasio Pertumbuhan.